Tools Allowing Independent Visualization and Genetic Manipulation of Drosophila melanogaster Macrophages and Surrounding Tissues. Issue 3 (1st March 2018) - Gyoergy, Attila; Roblek, Marko; Ratheesh, Aparna; Valoskova, Katarina; Belyaeva, Vera; Wachner, Stephanie; Matsubayashi, Yutaka; Sánchez-Sánchez, Besaiz J; Stramer, Brian; Siekhaus, Daria E
Abstract: Drosophila melanogaster plasmatocytes, the phagocytic cells among hemocytes, are essential for immune responses, but also play key roles from early development to death through their interactions with other cell types. They regulate homeostasis and signaling during development, stem cell proliferation, metabolism, cancer, wound responses, and aging, displaying intriguing molecular and functional conservation with vertebrate macrophages. Given the relative ease of genetics in Drosophila compared to vertebrates, tools permitting visualization and genetic manipulation of plasmatocytes and surrounding tissues independently at all stages would greatly aid a fuller understanding of these processes, but are lacking. Here, we describe a comprehensive set of transgenic lines that allow this. These include extremely brightly fluorescing mCherry-based lines that allow GAL4-independent visualization of plasmatocyte nuclei, the cytoplasm, or the actin cytoskeleton from embryonic stage 8 through adulthood in both live and fixed samples even as heterozygotes, greatly facilitating screening. These lines allow live visualization and tracking of embryonic plasmatocytes, as well as larval plasmatocytes residing at the body wall or flowing with the surrounding hemolymph. With confocal imaging, interactions of plasmatocytes and inner tissues can be seen in live or fixed embryos, larvae, and adults. They permit efficient GAL4-independent Fluorescence-Activated Cell Sorting (FACS) analysis/sorting of plasmatocytes throughout life. To facilitate genetic studies of reciprocal signaling, we have also made a plasmatocyte-expressing QF2 line that, in combination with extant GAL4 drivers, allows independent genetic manipulation of both plasmatocytes and surrounding tissues, and GAL80 lines that block GAL4 drivers from affecting plasmatocytes, all of which function from the early embryo to the adult.